OP0189 Long term work disability in anti-TNF therapy treated patients with psoriatic arthritis: A population-based cohort study. (23rd January 2014) - Kristensen, L.; Englund, M.; Geborek, P.; Neovius, M.; Askling, J.; Jacobsson, L.T.; Petersson, I.
Abstract : Background: Reduced work ability leading to sick leave is a common consequence of psoriatic arthritis (PsA). TNF-antagonist therapy has been a major advance in treating several aspects of PsA. Little is known about the impact of TNF treatment on long term work disability in PsA. Objectives: To study proportions of long term sick leave and disability pension before and after TNF-antagonist therapy in PsA patients. Methods: Using the population-based South Swedish Arthritis Treatment Group register, we identified 191 PsA patients (median age 43years, range 18-58y, 55% men), who between Jan 2003 and Dec 2007 (allowing for a complete 4 year follow-up period) started treatment with adalimumab, etanercept, or infliximab. We linked data to the payment register by the Swedish Social Insurance Agency and calculated the proportion on any sick leave in 30-day-intervals from 12 months before treatment start until 3 years after. For each PsA patient we randomly selected 4 reference subjects from the general population matched for age, sex, area of residence, and date of inclusion. Results: At treatment initiation 67% of the PsA patients were either on sick leave or received disability pension of any degree from part time thru full time. During the first 12 months after treatment start this fraction dropped to 58%, and remained at 57% after 3 years (p<0.001). Comparing PsA patients to the general population, the relative risk of being work disabled at treatment start, 12 months, and 3 years after treatment start was 4.2 (95% CI 3.4, 5.1), 3.7 (3.0, 4.5), and 3.4 (2.7, 4.2), respectively. Patients withdrawing from therapy during the follow-up period compared to patients sustaining treatment had the same baseline risk of being work disabled (69 vs 64%), but a 50% increased risk after the 3 year observational period (73 vs 53%; relative risk 1.5 [95% CI] 1.2, 1.8 for comparison between withdrawers to sustainers). Conclusions: There is a decline in work disability during the first 12 months after initiation of TNF-antagonist treatment in PsA patients not explained by societal factors or secular trends. This decline was sustained for the following 3 years. Patients withdrawing from therapy have a 50% increased risk of being work disabled than patients remaining on therapy. Disclosure of Interest: L. Kristensen Consultant for: Abbott, BMS, Pfizer, MSD, Mundipharma, M. Englund: None Declared, P. Geborek: None Declared, M. Neovius: None Declared, J. Askling: None Declared, L. Jacobsson Consultant for: Abbott, BMS, Pfizer, MSD, I. Petersson Consultant for: Abbott, Pfizer, MSD